PLANT- PARASITIC NEMATODES ASSOCIATED WITH CROP OF TAGETES ERECTA IN VIRU DISTRICT, LA LIBERTAD, PERU - Murga - Gutiérrez, Santos Nélida (2007)
The general, frequency and population density of plant-parasitic nematodes associated with Tagetes erecta crops (marigold) in the District of Viru, La Libertad, Peru, were determined. Soil and root samples were collected between March and December 2002, from 14 planted fields. Nematodes were extracted from soil samples by the Christie and Perry’s technique, and from root samples by the modified Baermann’s technique. The roots were also stained for detection of endoparasitic nematodes. Ten genera of plant-parasitic nematodes were found associated with crop of T. erecta in Viru district, which in decreasing order of frequency of fields with each genus extracted from soil were: Criconemoides 85,7 %, Helicotylenchus 78,6 %, Tylenchus 78,6 %, Meloidogyne 71,4 %, Hemicycliophora 64,3 %, Aphelenchoides 57,1 %, Trichodorus 35,7 %, Paratylenchus 28,6 %, Tylenchorhynchus 28,6 % and Pratylenchus 21,4 % and those extracted from roots were: Meloidogyne 64,3 %, Helicotylenchus 42,9 % and Criconemoides 28,6 %. The first three genera showed the highest population densities. Meloidogyne spp. were found inside the tissue of some galls and mostly presented immature forms and null or scarce production of eggs.